"This Place Belongs to Us": Historic Contexts as a Mechanism for Multivocality in the National Register. Issue 3 (July 2022) - Hanson, Kelsey E.; Baumann, Steve; Pasqual, Theresa; Seowtewa, Octavius; Ferguson, T. J.
Abstract : Since the creation of the National Register of Historic Places, determining eligibility for listing on it has become the fundamental process driving archaeology in the United States. This process affects how archaeological sites are identified, recorded, evaluated, and ultimately how they are protected. Yet less than 6% of properties on the National Register are archaeological sites. Although scholars often lament the rigidity of the National Register and its eligibility criteria, notable revisions in National Park Service guidance pave the way for important changes. One of the National Register's most pervasive and fundamental concepts—the historic context—remains deeply undertheorized when compared to more familiar terms like "significance" and "integrity." In this article, we argue that archaeologists are well positioned to reinvigorate the National Register by using historic contexts as a mechanism for recognizing layered relationships to places. Using an example from the multivocal nomination of the Inscription Rock Archaeological District as a case study, we argue that the oft-neglected concept of the historic context can be used to commemorate multivocality, moving from one national history to the production of multivocal national histories.